Pengaruh Struktur Modal, Kebijakan Dividen terhadap Nilai Perusahaan dengan Resiko Bisnis sebagai Moderasi pada Perusahaan Manufaktur BEI Periode 2018-2020 - Berar Fathia Geralin; Eko Purwanto (LPPM Institut Nasional Laa Roiba Bogor, 2023)
The value of the company is reflected in the company's performance in the share price which is built by supply and demand in the capital market, and reflects the public's evaluation of the company's performance. This study aims to prove (1) the effect of capital structure on firm value, (2) the impact of dividend policy on firm value, (3) the relationship between business risk in moderating capital structure and firm value, and (4) the impact of business risk on firm value. The moderating effect of the relationship between dividend policy and firm value. This research took 12 manufacturing companies on the Indonesia Stock Exchange from 2018 - 2020 as research objects, and the sampling technique used the purposive sampling method, so that a sample of 36 companies was obtained. The data analysis method is Moderated Regression Analysis (MRA). The results of the study prove that Capital Structure has a positive insignificant impact on Firm Value, Dividend Policy has a significant positive impact on Firm Value, Business Risk moderates the relationship between Capital Structure and Firm Value, and Business Risk moderates the relationship between Dividend Policy and Firm Value. Keywords: Capital Structure, Dividend Policy, Firm Value and Business Risk.